THE EFFECT OF VARIED STEAMING TIME ON THE QUALITY OF KATSUOBUSHI (WOODY SMOKED FISH) SKIPJACK (Katsuwonus pelamis) - Syahputra, Alias; Mus, Sukirno; Leksono, Tjipto (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACTThis research was aimed to observetheeffect of varied steaming timeon the quality of katsuobushiskipjack (Katsuwonus pelamis)based on sensory evaluation (appearance, aroma, taste, texture), proximate analysis (the content of moisture, protein, and ash), content of total phenol, the Total Plate Count of bacteria, and identificationof fungi. The experimental design used in this study was a Randomized Complete Design (RCD). The treatment conducted was the varied steaming timeat a temperature of 100-105°C, consisted of 30 minutes (T1), 60 minutes (T2) and 90 minutes (T3). The results showed that the katsuobushi processed by steaming for 30 minutes (T1) wasshowing as the best treatment, indicated by the highest organoleptic value. The value of the consistencewas 7.7, characterized with clean, shiny colors, without cracks; the value of the texture was 7.8,characterized with hard, not easily broken; the value aroma was 7.5, characterized withspecific aroma of katsuobushi;and the taste value was 7.9,characterized withvery tasty and savory taste. The content of moisture was 11,99%, protein was 77,44%, ash was 0,60%, and the content of total phenol was 0,0024%. The Total number of bacteria Plate Count was 5.6 x 103 cfu/g,mean while the type of fungigrowth identified wasAspergillus sp.Keywords:Aspergillus sp., katsuobushi, skipjack, steaming time